2017
DOI: 10.12788/jhm.2736
|View full text |Cite
|
Sign up to set email alerts
|

Planning and Designing the Improving Addiction Care Team (IMPACT) for Hospitalized Adults with Substance Use Disorder

Abstract: People with substance use disorders (SUD) have high rates of hospitalization and readmission, long lengths of stay, and skyrocketing healthcare costs. Yet, models for improving care are extremely limited. We performed a needs assessment and then convened academic and community partners, including a hospital, community SUD organizations, and Medicaid accountable care organizations, to design a care model for medically complex hospitalized patients with SUD. Needs assessment showed that 58% to 67% of participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
143
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 132 publications
(144 citation statements)
references
References 18 publications
0
143
1
Order By: Relevance
“…© 2018 Society of Hospital Medicine cludes a hospital-based, interprofessional addiction medicine consultation service and rapid-access pathways to community addiction care after hospitalization. 17 . IMPACT is an intensive intervention that includes SUD assessments, withdrawal management, medications for addiction (eg, methadone, buprenorphine induction), counseling and behavioral SUD treatment, peer engagement and support, and linkages to community-based addiction care.…”
Section: Measurementsmentioning
confidence: 99%
“…© 2018 Society of Hospital Medicine cludes a hospital-based, interprofessional addiction medicine consultation service and rapid-access pathways to community addiction care after hospitalization. 17 . IMPACT is an intensive intervention that includes SUD assessments, withdrawal management, medications for addiction (eg, methadone, buprenorphine induction), counseling and behavioral SUD treatment, peer engagement and support, and linkages to community-based addiction care.…”
Section: Measurementsmentioning
confidence: 99%
“…Hospitalization can be a reachable moment to initiate and coordinate SUD care. Although medical and surgical inpatients do not come to the hospital seeking addiction care, a study of hospitalized adults at our hospital found that over half of people with high-risk alcohol use and over two-thirds of people with high-risk drug use reported wanting to cut back or quit (24). Interventions to improve post-discharge SUD treatment engagement are likely to improve outcomes for people with SUD.…”
Section: Introductionmentioning
confidence: 98%
“…We implemented a previously described interprofessional hospital-based addiction medicine consult service called the Improving Addiction Care Team (IMPACT) (8,24,31,32). IMPACT engages adults with opioid, alcohol, methamphetamine, and other substances (excluding tobacco use disorder alone) during the reachable moment of hospitalization and provides rapid-access pathways to community SUD treatment and harm reduction support.…”
Section: Introductionmentioning
confidence: 99%
“…The national opioid crisis has brought with it a renewed focus on the integration of addiction care into medical settings. Though integration into primary care settings may have represented the first wave of quality improvement in this area-with the emergence of Screening, Brief Intervention, and Referral to Treatment (SBIRT)-the past 5 years have witnessed the expansion of addiction consult services in general medical hospitals [1][2][3][4][5][6]. Such systemic integration efforts are critical considering the majority of patients with substance use disorders (SUD)-greater than 90%-do not seek specialty addiction treatments but instead seek treatment in hospitals and emergency rooms for the medical complications of substance use [7].…”
mentioning
confidence: 99%